MODEL PENGEMBANGAN MOTIVASI DAN PARTISIPASI ANGGOTA DALAM MENINGKATKAN PELAYANAN SERTA KINERJA KOPERASI DI KPRI UNIVERSITAS JEMBER - Sundari, Sri; Anggraeni, Oktanita Jaya (Profit: Jurnal Adminsitrasi Bisnis, 2007)
This paper tries ti find out a model in upgrading motivation and participation of cooperation members as one way to increase their service quality. In General, cooperation has three goals, i.e business success, members success, and community development success. The are some barriers faced by them in catching their purposes, i.e limited modal, technology, market access, production quality and simple management. Basically, members of cooperation have to positions (dual identity), as owner and user of cooperation. Consequantly, a cooperation success means that the members can fulfill their both needs as the user and the owner